2021
DOI: 10.1111/tri.13870
|View full text |Cite
|
Sign up to set email alerts
|

Living kidney donor evaluation for all candidates with normal estimated GFR for age

Abstract: Multiple days assessments are frequent for the evaluation of candidates to living kidney donation, combined with an early GFR estimation (eGFR). Living kidney donation is questionable when eGFR is <90 ml/min/1.73 m 2 (KDIGO guidelines) or 80 ml/min/1.73 m 2 (most US centres). However, age-related GFR decline results in a lower eGFR for older candidates. That may limit the number of older kidney donors. Yet, continuing the screening with a GFR measure increases the number of eligible donors. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore, CT measurement of KD can improve the accuracy of GFR calculations. This is especially true for living kidney transplant donors who need accurate renal GFR partitioning (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT measurement of KD can improve the accuracy of GFR calculations. This is especially true for living kidney transplant donors who need accurate renal GFR partitioning (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Gaillard et al (82) in 2021 studied 1,825 French LKDs. After a mean follow-up of almost 6 years, they found that in donors younger than 45 years post-donation eGFR, absoluteand relative-eGFR variation were not different among the three groups, normal for age (Sage), higher than 90 (S90), or 80(S80) ml/min/1.73 m 2 .…”
Section: Renal Function After Donationmentioning
confidence: 99%